2003
DOI: 10.1590/s0102-35862003000200011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and malnutrition: why are we not winning this battle?

Abstract: Objectives:Objectives: Objectives: Objectives: To review the mechanisms involved in the origin of malnutrition in patients with chronic obstructive pulmonary disease (COPD), and to make a systematic review of randomized controlled studies, to clarify the contribution of nutritional supplementation in patients with stable COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
(57 reference statements)
0
4
1
3
Order By: Relevance
“…It found that nutritional support leads to improvements in nutritional intake, body weight, muscle mass (MAMC), fat mass (skinfold thickness), and an improvement in peripheral muscle strength (handgrip strength). These findings are completely in contrast with those of previous reviews and meta-analyses (6,7,42,63,64), which reported no significant differences between intervention and control groups. The previous meta-analyses (6,7,42) did not examine changes in dietary intake.…”
Section: Discussioncontrasting
confidence: 99%
“…It found that nutritional support leads to improvements in nutritional intake, body weight, muscle mass (MAMC), fat mass (skinfold thickness), and an improvement in peripheral muscle strength (handgrip strength). These findings are completely in contrast with those of previous reviews and meta-analyses (6,7,42,63,64), which reported no significant differences between intervention and control groups. The previous meta-analyses (6,7,42) did not examine changes in dietary intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Swallowing disorders can also lead to other complications, including dehydration, aspiration pneumonia, or airway obstruction. 34 …”
Section: Literature Reviewmentioning
confidence: 99%
“…9 In addition to the uncertainty about the causal links between malnutrition and COPD, there are controversies about how effective nutritional support is in this patient group. Previous reviews and meta-analyses [10][11][12] suggested that malnutrition fails to respond to nutritional treatment in COPD finding no significant improvements in anthropometric or functional measures. These conclusions have been challenged by several randomized, controlled trials (RCT), [13][14][15][16] and a recently published meta-analysis concluded that nutritional support was able to significantly increase nutritional intake (energy and protein), which was associated with a significant improvement in a variety of anthropometric measures.…”
Section: Introductionmentioning
confidence: 99%